Continuous Improvement dengan PDCA pada Produksi Sabun Batang di PT XYZ - Kesuma, Raihan; Muhimatul Khoiroh, Siti (Fakultas Teknik UMRI, 2024)
PT XYZ is a multinational company operating in the Fast Moving Consumer Goods (FMCG) sector. The existence of one of the production lines which frequently experiences downtime means that the Company is unable to maximize the fulfillment of consumer demand. This research aims to enhance the efficiency and effectiveness of machine equipment particularly focusing on Line 2 in bar soap production. In this research, an analysis was carried out using Overall Equipment Effectiveness (OEE) and Six Big Losses methods as the basis for the calculation. The stages in this research are identifying the cause of the problem using a fishbone diagram and the 5 Whys technique, as well as designing a repair solution using the PDCA cycle. The results of this research show that The average suction cup setting for the period August 2023-February 2024 before repairs were carried out was 1.68% affecting OEE, and after repairs were carried out for 3 weeks it managed to decrease to 1.37% with a difference of 0.31%. The calculation of Overall Equipment Efficiency (OEE) results has increased from the average for the period August 2023-February 2024 before the improvement was 60.10%, then improvements were carried out for 2 weeks and managed to increase to 64.20% with a difference of 4.10%.